Dental age estimation of Malaysian Indian children and adolescents: Applicability of Chaillet and Demirjian’s modified method using artificial neural network - Safar Sumit Bunyarit; Phrabhakaran Nambiar; Murali Naidu; Muhammad Khan Asif; Rozaida Yuen Ying Poh (Taylor & Francis, 2024)
Indexed by WOS/Scopus/ERA